Legal Status of a Wife Leaving Her Husband and Vice Versa in Contextual Fiqh Studies: A Pre-Divorce Analysis - Haddad Ulum Harahap; Muhammad Fadhlan Is; Amrar Mahfuzh Faza; Muhamad Hasan Sebyar (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
The issue of a wife leaving her husband or vice versa before an official divorce is a critical topic in Islamic jurisprudence (fiqh), raising legal, ethical, and social concerns. This study examines the legal status of such separations through the lens of various schools of thought (madhhab), analyzing spousal rights and obligations in pre-divorce contexts. Employing a qualitative method, it draws from primary Islamic legal sources, as well as contemporary statutory frameworks in Muslim-majority countries. Findings reveal that Islamic law distinguishes between justified and unjustified separation. A wife who separates without valid reason may be deemed nusyuz, which affects her right to nafaqah (maintenance), while a husband remains responsible for financial obligations until the divorce is finalized. Conversely, if separation is due to harm, negligence, or abuse, mechanisms such as fasakh (annulment) or khulu' (divorce initiated by the wife) may be pursued under Islamic principles. These doctrines aim to protect the rights of both parties and prevent injustice in marital relationships. From the perspective of civil law, legal separation is not explicitly codified, but courts may provide temporary arrangements through mediation and judicial orders. Customary law often manages informal separations through community mediation and traditional consensus. In Indonesia, religious courts (peradilan agama) handle pre-divorce separations as part of divorce proceedings, emphasizing mediation and evaluating interim living arrangements, financial duties, and child custody. Beyond legal analysis, the study highlights broader social consequences: women and children are often left vulnerable during informal separations, while unresolved conflicts can fragment social harmony